Data acquisition for optical tomography system based on complementary metaloxide semiconductor area image sensor - Idroas, Mariani (2014)
This paper describes the development of a low power consumption and low cost data acquisition system (DAQ), which is used to capture images for optical tomography system. The system used a Complementary Metal Oxide Semiconductor (CMOS) image sensor as an optical sensor. Arduino Mega 2560 is used as the control circuit to produce its own DAQ. To test the functionality of the system, several tests were conducted to capture the shape of the object. The results showed that the images of the objects were successfully being reconstructed. With 5.2µm^2 of pixel size, this will produce high resolution reconstructed image for the optical tomography.